2013
DOI: 10.1016/j.jinteco.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Lumpy countries, urbanization, and trade

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
1
19
1
1
Order By: Relevance
“…This is also appropriate because, as we explained in the Introduction, regional urbanisation and sectoral composition or specialisation are probably not independent. On a rather general level, we know for instance that more urbanised areas are more and differently specialised (see Brakman and van Marrewijk, 2013). Concentration of specific factors of production could determine specialisation patterns, which in turn determines regional resilience.…”
Section: The Joint Effects Of Urbanisation and Sectoral Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also appropriate because, as we explained in the Introduction, regional urbanisation and sectoral composition or specialisation are probably not independent. On a rather general level, we know for instance that more urbanised areas are more and differently specialised (see Brakman and van Marrewijk, 2013). Concentration of specific factors of production could determine specialisation patterns, which in turn determines regional resilience.…”
Section: The Joint Effects Of Urbanisation and Sectoral Compositionmentioning
confidence: 99%
“…More importantly, it would restrict our sample to only 163 regions from 12 countries (results are available from the authors upon request).2 This connection also relates to the Heckscher-Ohlin trade models applied to smaller spatial scales than countries (see Deardorf, 1992, 1993). They use the term 'lumpiness' for the uneven distribution of factors of production over space, seeBrakman and van Marrewijk (2013) for some empirical support.3 The number of regions for which we have information on both urbanisation and unemployment available varies from 254 regions in 2008 to 271 regions in 2012. Further information requirements reduce the number of incorporated regions in the formal analysis to 207, see below.4 These are unweighted regional averages.…”
mentioning
confidence: 99%
“…En primer lugar, la distribución urbana desigual es un factor que determina la estructura del comercio (Brakman y Van Marrewijk, 2013). Algunos estudios presentan evidencia de la concentración regional del trabajo cualificado que induce un número abundante de trabajadores cualificados a recibir salarios bajos y, por lo tanto, a especializarse en la producción de bienes que requieren un alto grado de cualificación (OMC, 2013).…”
Section: Comercio Internacional Urbanización Y Crecimiento Económicounclassified
“…Finally, we included urbanization as another prospective determinant of trade. Brakman and Marrewijk (2013) and Smart and Smart (2003) have suggested that trade patterns may be influenced by level of urbanization, as urbanization may increase mobility and promote networks (Brakman & Marrewijk, 2013).…”
Section: The Datamentioning
confidence: 99%